Synthesis and Characterization of 2D‐D‐π‐A‐Type Organic Dyes Bearing Bis(3, 6‐di‐tert‐butylcarbazol‐9‐ylphenyl)aniline as Donor Moiety for Dye‐Sensitized Solar Cells. Issue 13 (13th March 2013) - Khanasa, Tanika; Jantasing, Nittaya; Morada, Somphob; Leesakul, Nararak; Tarsang, Ruangchai; Namuangruk, Supawadee; Kaewin, Tinnagon; Jungsuttiwong, Siriporn; Sudyoadsuk, Taweesak; Promarak, Vinich
Abstract: A series of novel 2D‐D‐π‐A‐type organic dyes, namely CCTTnA ( n = 1–3), bearing bis(3, 6‐di‐ tert ‐butylcarbazol‐9‐ylphenyl)aniline as an electron‐donor moiety (2D‐D), oligothiophene segments with a number of thiophene units from one to three units as π‐conjugated spacers (π), and cyanoacrylic acid as the electron acceptor (A) were synthesized and characterized as dye sensitizers for dye‐sensitized solar cells (DSSCs). These compounds exhibit high thermal and electrochemical stability. Detailed investigations of these dyes reveal that both peripheral carbazole donors (2D) have beneficial influence on the red‐shifted absorption spectrum of the dye in solution and dye adsorbed on TiO2 film, and the broadening of the incident monochromatic photon‐to‐current conversion efficiency (IPCE) spectra of the DSSCs, leading to enhanced energy conversion efficiency ( η ). Among these dyes, CCTT3A shows the best photovoltaic performance, and a maximal incident monochromatic photon‐to‐current conversion efficiency (IPCE) value of 80 %, a short‐circuit photocurrent density ( Jsc ) of 9.98 mA cm –2, open‐circuit voltage ( Voc ) of 0.70 V, and fill factor (FF) of 0.67, corresponding to an overall conversion efficiency η of 4.6 % were achieved. This work suggests that organic dyes based on this type of donor moiety or donor molecular architecture are promising candidates for improved performance DSSCs. Abstract : New 2D‐D‐π‐A‐type organic dyes incorporating bis(3, 6‐di‐ tert ‐butylcarbazol‐9‐ylphenyl)aniline as an electron‐donor moiety show great potential as sensitizers for dye‐sensitized solar cells.